The greedy triangle - Burns, Marilyn, 1941-; Silveria, Gordon (New York : Scholastic, 1994)
Dissatisfied with its shape, a triangle keeps asking the local shapeshifter to add more lines and angles until it doesn't know which side is up.
"A Marilyn Burns brainy day book.".
Booklist.
Publisher's Weekly.
School Library Journal.
4.7
K-3
Keywords: Self-acceptance -- Fiction; Shape -- Fiction; Self-acceptance -- Fiction; Shape -- Fiction